The effect of planting spacing on Pinus patula stem straightness, microfibril angle and wood density. (2nd March 2018) - Erasmus, Justin; Kunneke, Anton; Drew, David M; Wessels, C Brand
Abstract: Improved growth rates and shorter rotation ages have caused a reduction in the stiffness of structural lumber from South African-grown pine plantations. Microfibril angle (MFA) and wood density are known to be two wood properties that influence wood stiffness. Therefore, the objective of this study was to determine the effect of planting spacing of Pinus patula trees, on the MFA and wood density, as well as stem straightness. A total of 171 trees from four spacing treatments (403, 1097, 1808 and 2981 stems ha −1 ) from an 18-year old experimental P. patula plantation located in Mpumalanga, South Africa, were analysed for wood density, MFA, and ring width. A sub-sample of 81 trees was scanned for tree form using a terrestrial laser scanner. A non-linear mixed-effects model using a power function was developed to model MFA and wood density as a function of ring number and ring width. Planting spacing had a highly significant effect on stem straightness with the most widely spaced trees having the worst mean stem straightness. However, the stem straightness did not increase consistently with increasing stems ha −1 . The dynamic modulus of elasticity of standing P. patula trees increased greatly with closer spacing – more so than any other species reported in literature. The mixed model showed that, after accounting for differences due to ring number and ring width, spacing treatment had a significant effect on both the initial MFA and its rate of change with age. For wood density, this remaining effect of spacing treatment was only displayed in its radial rate of change. Based on these results, it seems as if planting spacing has great potential as a management intervention to improve the mechanical wood properties and in certain cases also the stem straightness of South African-grown P. patula at final harvest.